EKSISTENSI MADRASAH ALIYAH SEBAGAI LEMBAGA SATUAN PENDIDIKAN MENENGAH DALAM PERSPEKTIF KEMAJUAN IPTEK DAN DAYA SAING - Hairil Anwar; Zakaria Zakaria (Manajer Pendididikan, 2019)
The purpose of this study is to describe existence of Islamic High School as institute of medium education institution in the perspective performance of the scientific and competitive. The method of this research is qualitative descriptive study. The subject of the this research were the Head of the Regional Office of The Religious Ministry of Bengkulu Province, principal of Public Islamic High School 2 Bengkulu City, vice principals, and teachers. The data was obtained with observation, documentation, and interview. Then the collected data analyzed by qualitative technique as proposed by Miles and Huberman that is data reduction, data presentation and conclusion. The results showed that the existence of Islamic High School viewed from the vision and mission, national education standard, SWOT, competitiveness, road map, and the role of Regional Office of Ministry of Religion open to the progress of science and technology and competition among other educational institutions equivalent. The conclusion of the research shows that the existence of Islamic High School not fully able to respond to the progress of Science and Technology and compete with other equivalent educational institutions, but should be a serious concern for the existence of Islamic schools can be maintained. Researchers suggest that all educators and education work more maximally in showing the existence of islamic high school in perspective of science and technology progress and competitiveness, so as to compete with other equivalent educational institutions.